Managing endothelial dysfunction in COVID‐19 with statins, beta blockers, nicorandil, and oral supplements: A pilot, double‐blind, placebo‐controlled, randomized clinical trial - Kamal Matli; Abdulrahman Al Kotob; Wassim Jamaleddine; Soad Al Osta; Pascale Salameh; Rami Tabbikha; Nibal Chamoun; Ahmad Moussawi; Jean‐Michel Saad; Gibran Atwi; Tarik Abu Saad; Omar Jamal; et al. (Clinical and Translational Science, 2022)
Abstract Coronavirus disease 2019 (COVID‐19) is associated with endothelial dysfunction. Pharmacologically targeting the different mechanisms of endothelial dysfunction may improve clinical outcomes and lead to reduced morbidity and mortality. In this pilot, double‐blind, placebo‐controlled, randomized clinical trial, we assigned patients who were admitted to the hospital with mild, moderate, or severe COVID‐19 infection to receive, on top of optimal medical therapy, either an endothelial protocol consisting of (Nicorandil, L‐arginine, folate, Nebivolol, and atorvastatin) or placebo for up to 14 days. The primary outcome was time to recovery, measured by an eight category ordinal scale and defined by the time to being discharged from the hospital or hospitalized for infection‐control or other nonmedical reasons. Secondary outcomes included the composite outcome of intensive care unit (ICU) admission or the need for mechanical ventilation, all‐cause mortality, and the occurrence of side effects. Of 42 randomized patients, 37 were included in the primary analysis. The mean age of the patients was 57 years; the mean body mass index of study participants was 29.14. History of hypertension was present in 27% of the patients, obesity in 45%, and diabetes mellitus in 21.6%. The median (interquartile range) time to recovery was not significantly different between the endothelial protocol group (6 [4–12] days) and the placebo group (6 [5–8] days; p value = 0.854). Furthermore, there were no statistically significant differences in the need for mechanical ventilation or ICU admission, all‐cause mortality, or the occurrence of side effects between the endothelial protocol group and the placebo group. Among patients hospitalized with mild, moderate, or severe COVID‐19 infection, targeting endothelial dysfunction by administering Nicorandil, L‐arginine, Folate, Nebivolol, and Atorvastatin on top of optimal medical therapy did not decrease time to recovery. Based on this study’s findings, targeting endothelial dysfunction did not result in a clinically significant improvement in outcome and, as such, larger trials targeting this pathway are not recommended.